Christmas letters [compact disc, unabridged] - Macomber, Debbie (Blossom street, 2006)
Katherine O'Connor writes Christmas letters for other people. Dr. Wynn Jefferies is a renowned child psychologist to whom Christmas means lies and deception. Although they disagree about practically everything, they discover that love means accepting your differences.